First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species - Ranjith, A.p.; Belokobylskij, Sergey A.; Nasser, M. (Zootaxa, 2019)
The Australasian braconine genus Undabracon Quicke, 1986 is recorded from the Indian subcontinent for the first time and we describe a new species, U. binduae Ranjith sp. nov. An illustrated key is provided for all the extant species together with the re-illustration of the species U. jacundus (Enderlein, 1920).